The Linguistic Level of the Teacher’s Teaching Perspective: Analysis and Reflexion - Cabezas Holgado, Emilio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2017)
The present work includes the curricular contents of the linguistic subjects that must be addressed by the student of the Master Degrees in E. Infantil and E. Primaria. In this sense, the concepts that the future teacher of children's cycle integrates from the subject of compulsory training Language Acquisition and Development and the analyzes that the student of Primary School must face through the program of Spanish Language. On the other hand, the methodology that corresponds to one or another level will be established according to the particularities of each linguistic plane: phonic, morphosyntactic, semantic and pragmatic.
Keywords: linguistics; education; teaching; grammar; didactics